Landscapes north of Petra: the Petra Area and Wādī Silaysil Survey (Brown University Petra Archaeological Project, 2010-2011) - Alcock , Susan E.; Knodell, Alex R. (Proceedings of the Seminar for Arabian Studies, 2012)
Since 2010 the Petra Area and Wādī Silaysil Survey (PAWS) has undertaken a systematic regional survey of some of the immediate environs of Petra, as part of the wider Brown University Petra Archaeological Project (BUPAP). This survey is designed to investigate the changing natural and cultural landscapes of the Petra area in diachronic fashion and from a multidisciplinary perspective, employing intensive pedestrian survey methods more familiar in the Mediterranean than the Middle East. The first season (2010) focused on three areas, all north of Petra proper: Wādī Baqʿah; the vicinity of Little Petra and the Neolithic and Islamic villages at Bayḍā; and Wādī Silaysil, site of a Nabataean sanctuary and settlement (Raʾs al-Silaysil). The second season (2011) prioritized closing gaps between these three zones and expanded coverage eastwards towards the Sharā Mountains. The study region contained several known sites and features, some even cursorily published. Shifting from a site-oriented to a landscape perspective, however, we recovered evidence of human activity from the Palaeolithic to the present, as well as several unexpected patterns: a wide distribution of late prehistoric lithics, an Iron Age presence, and an early (Hellenistic) occupation at Raʾs al-Silaysil and several other locations throughout the landscape. We also initiated geological and ethnographic studies, as well as programmes of architectural study and route-based analysis of the built and natural environment. This paper summarizes the goals, methods, and results of PAWS.